PEMBUATAN PASTA DAN PEMBENTUKAN LAPISAN TIPIS HIDROKSI APATIT KARBONAT - Samah, Selfa Dewati; Arief, Syukri; Jamarun, Novesar (Universitas Andalas, 2014)
Â ABSTRACTPaste of Carbonated Hydroxyapatite (CHA) as a biocompatible material that can be used in thebone and teeth repair has been developed on preparation of thick film. CHA paste was preparedby mixing precipitate of CHA with CaSO4 and polyethylene glycol (PEG) in 2-propanol assolvent. Paste was deposited on substrate to get thick films by screen printing method. X raydiffraction (XRD) analysis has shown hexagonal crystal structure and crystal size of CHAacquired 7,2 nm by Scherrerâ€™s method. Fourier Transform Infrared (FTIR) analysis has shownabsorption spectra which indicating phosphate, carbonate, and hydroxide group. Size of thiscomposite particles analyzed by PSA (particle size analyzer) about 3Î¼m and pore size was 0.44-0.49 nm obtained from BET analysis, increased with the addition of CaSO4 (0.44 to 0,49 nm).Rephrase PEG was found as an adhesive and homogenize paste on substrat surface. In addition,CHA paste also potentially can be used as bone cement.Keywords : Paste, thick film, carbonated hydroxyapatite